Implementasi Website Sekolah untuk Optimalisasi Promosi dan Administrasi Internal di SMK Jayanegara - Primaadi Airlangga; Sujono Sujono; Novan Maulana; Ifham Adlan; Diana Khusniyah; Jauhar Imtikhan (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
The rapid development of information technology has urged schools not only to provide learning services but also to utilize digital media for promotion and administrative management. One of the key instruments in this digital transformation is the school website, which functions as a medium for information transparency, achievement publication, and strengthening of internal services. This community service program was implemented in August 2025 at SMK Jayanegara Bicak, Trowulan, Mojokerto, using a participatory approach involving teachers, staff, and school leaders. The stages included needs assessment, menu design, development of a website using CodeIgniter 3, training, mentoring, implementation, and evaluation. The results showed that the school website was successfully developed with a simple and user-friendly interface, providing structured information on school profiles, facilities, achievements, activities, and online student admission services. The website was also utilized for internal administration such as document archiving and new student registration. Training improved teachers’ and staff’s digital skills, enabling them to manage web content independently. The program’s impact included improved information transparency, enhanced school promotion, administrative efficiency, and strengthened digital literacy among human resources. Therefore, the school website proved to be not only an external communication tool but also a strategic instrument for modern and sustainable school governance.